Combination of microdissection and single cell quantitative real-time PCR revealed intercellular mitochondrial DNA heterogeneities in fibroblasts of Kearns-Sayre syndrome patients - Kummer, Susann; Wilichowski, Ekkehard (Mitochondrion, 2018)
Kearns-Sayre syndrome (KSS) is a multisystemic disorder marked by aerobic cell metabolism dysfunction. Fibroblasts derived from KSS patient skin biopsy exhibit heterogeneous occurrence of mitochondrial genomes as those circular DNA molecules partially carry the common deletion. In our approach, we aim to evaluate the intercellular alterations in respect to mitochondrial DNA integrity by laser capture microdissection and multiplex quantitative real-time PCR in single cells. The obtained results give new insights into the understanding of mitochondrial genetics, e.g. postulated sorting of damaged mitochondria, and heterogeneity of cells. Further, we discuss the relevance of intercellular heterogeneities for human mitochondrial disorders in general.
Gesehen am 17.04.2020